2018
DOI: 10.15171/ijoem.2018.1176
|View full text |Cite
|
Sign up to set email alerts
|

Can Job Control Ameliorate Work-family Conflict and Enhance Job Satisfaction among Chinese Registered Nurses? A Mediation Model

Abstract: Background: Low job satisfaction is the most common cause of nurses' turnover and influ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
5
21
0
1
Order By: Relevance
“…Secondly, role conflicts was found to be negatively correlated with job satisfaction, which is consistent with previous reports [9,10,21]. The present study further demonstrated the presence of work-family-school role conflicts in RNs enrolled in a nursing education program.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Secondly, role conflicts was found to be negatively correlated with job satisfaction, which is consistent with previous reports [9,10,21]. The present study further demonstrated the presence of work-family-school role conflicts in RNs enrolled in a nursing education program.…”
Section: Discussionsupporting
confidence: 92%
“…The association between work-family conflict and job satisfaction was well cited in nursing literature [7][8][9]. Reducing conflict between family and work roles can improve the quality and productivity of nursing, which will in turn improve job satisfaction [8,10]. Both work-to-family and family-to-work role conflicts were found to be negatively correlated with job satisfaction, with work-to-family role conflict having a greater affect than family-to-work role conflict on job satisfaction among RNs in mainland China [7,9].…”
Section: Role Conflict and Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies show that nursing staff in most countries face a relatively unsatisfactory work environment, and experience a lot of work-related stress (Ding, 2018). These pressures include high mental and physical stress, scheduling or irregular shifts in working hours, limited promotion of work and social-emotional stress with respect to patients and partners (Ding et al, 2018;Ibrahim , 2016). The results showed that the amount of work pressure on nurses had negative consequences on their families and social problems and had caused disruption in social activities with their partners.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the amount of work pressure on nurses had negative consequences on their families and social problems and had caused disruption in social activities with their partners. This causes an increase in interpersonal conflict and affects their quality of life and satisfaction (Ding , 2018).…”
Section: Introductionmentioning
confidence: 99%